Kajian Partisipasi Masyarakat Dusun Bone Puteh Dalam Pengelolaan Sampah - Ni Made Nia Bunga Surya Dewi (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
Waste is an item or object that has used up its useful value and is always present in everyday life which is caused by activities that occur all the time, which also occurs in Bone Puteh Hamlet, Labuan Kertasari Village, Taliwang District, West Sumbawa Regency. Waste production is increasing every day in line with the increasing number of products and consumption patterns of society. What must be done to overcome this increase in waste volume is by: reducing the volume of waste from its source through community empowerment. The problem in community participation regarding waste management is related to the form of regulation in waste management in Bone Puteh Hamlet, what is the form and level of community participation in waste management. Research on community participation-based waste management in Bone Puteh Hamlet aims to: 1) Describe the form of community participation in Bone Puteh Village. 2) Describe the level of community participation in Bone Puteh Village where data collection techniques include interviews, observation and documentation, while data analysis uses descriptive qualitative techniques. Based on the results of the research, it is found that one form of community participation in efforts to improve the environment is by providing contributions of labor in the form of community service, mutual cooperation and participating in waste management. Apart from that, the community also holds a community meeting which is held once a month where the community carries out these activities without coercion. The level of community participation that occurs in Bone Puteh Hamlet is in a moderate category which means that the community participates but in its implementation it is still not optimal